Strength of diversification of investment portfolio without oil, Malaysian experience (reading development plans, vision 2020). - خويلدات, صالح; طرايش, معمر (Université de M'sila, 2017)
the Malaysian plans and policies since independence in 1957 until now, has focused on resources, and human capital, foreign direct investment ...for growth economic, the government implemented many strategies which aims at becoming a developed country by 2020, under the economic transformation programs Malaysia has lot of key areas to drive its economic revolution, this paper try to present the main plans of malaysian growth , as well, we try to give the future-looking outlook of 2020 vision (without oil industry).
Keywords: Malaysia, growth economic experiences, Malaysian 2020 vision.